A procura pelo pronto socorro: uma análise psicossocial da busca por saúde em grande metrópole - Ovelheiro, Tarsila Maria (2013)
This study aims to contribute with the understanding of the senses of searching for health in a large metropolis, using as local for research the adult emergency department of a large and high complexity hospital located at the north of Sao Paulo city. The theoretical research basis is the Social Psychology from Socio-Historical perspective. We presented a health concept meaning development process contextualization and the Brazilian public policies to attend it, in order to historically situate our research problem and highlight the inclusion/exclusion dialectic as a social dimension of illness/health that qualifies the suffering originated from this ethical-political process to express the historical, subjective and social processes synthesis, allowing overtaking the guiltiness appearance and individual responsibilities on manifestations and practices of the current health seeking. The information collection procedure was from ethnographic character with participating observation and interview with a guide. The interview analysis was oriented by Vygotsky reflections about sense, meaning and language subtext that indicates that the thinking doesn´t coincide directly with its verbalized expression, it started with the thematic emergent units related to health and Emergency Department search, highlighting the expressions that represents the affective-volitional bases: affections and motives. Observed: the individuals seeking for treatment at emergency department is related to their sufferings, emotions and, mainly, with the hope of finding an answer for those sufferings; and that the institution represents for them an excellence image through large technological resources, urgency treatment and population free access without the appointment requirement, in other words, it represents treatment, diagnosis and, with that, the fast and efficient cure